Fluid Selection and Plant Configuration of an ORC-biomass fed System Generating Heat and/or Power. (November 2016) - Pezzuolo, Alex; Benato, Alberto; Stoppato, Anna; Mirandola, Alberto
Abstract: The aim of the paper is to compare from an energetic, exergetic and economic viewpoint different plant configurations of Organic Rankine Cycles matched with biomass-fired boilers for electricity production or combined heat and power generation. To this purpose, a computer tool able to perform the fluid selection and plant layout optimization has been developed. The devices efficiency charts are used to predict the components performance while the fluid thermodynamic properties have been retrieved from two databases. Results show that Toluene guarantees the highest performance in both cases while the most suitable configuration is the recuperative one.